Coronary artery transplantation operations (review) - A. M. Morozov; A. N. Sergeev; E. M. Askerov; V. A. Kadykov; T. S. Alieva; E. A. Fisyuk (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Coronary artery transplantation operations are an effective method for the treatment of developmental anomalies and pathologies of the coronary arteries, which lead to a cascade of negative consequences. Pathologically altered coronary arteries cannot fully function normally and this condition leads to myocardial ischemia. Ischemic heart disease (CHD) is a chronic inflammatory disease that quickly leads to functional disorders in the body. CHD is mainly caused by atherosclerosis of the arteries and is the leading cause of death in most developed countries.The purpose of study. To study the operational possibilities of coronary artery transplantation.Materials and methods. In the course of this study, a review of foreign literature on the problem of surgical interventions on the coronary arteries was carried out, in addition, data from randomized controlled trials and controlled clinical trials were analyzed, which reported on various approaches to the treatment of pathologies of the heart vessels.Results. Coronary artery bypass grafting is most often performed in coronary heart disease caused by a sharp narrowing or occlusion of the lumen of the coronary artery. Coronary artery bypass grafting (CABG) is a major surgical operation, which consists in restoring blood circulation bypassing the stenotic area of the coronary artery using venous or arterial bypasses (grafts). At the same time, blood flow to the ischemic myocardium is restored, which leads to the restoration of the function and viability of the heart muscle. Coronary artery bypass grafting, as mentioned above, is a frequently performed surgical intervention, with almost 400,000 CABG surgeries performed annually, which proves its effectiveness in the treatment of coronary artery disease.Conclusion. This study proves the importance of coronary artery transplantation in the treatment of pathologies and anomalies of the arteries of the heart. There are several types of surgical interventions, and therefore it is necessary to approach each individual case individually and find the optimal solution. An important role in preventing postoperative complications and sudden cardiac arrest is played by careful preoperative diagnostics, including coronary angiography, echocardiography, computed tomography, and other methods. With careful preoperative diagnosis, a well-chosen operation strategy and postoperative prevention, it is possible to avoid repeated cardiac revascularization and achieve complete recovery of the patient with no complications for decades.